Governing the transition to renewable energy: A review of impacts and policy issues in the small hydropower boom. (February 2017) - Kelly-Richards, Sarah; Silber-Coats, Noah; Crootof, Arica; Tecklin, David; Bauer, Carl
Abstract: The transition to renewable energy technologies raises new and important governance questions. With small hydropower (SHP) expanding as part of renewable energy and climate mitigation strategies, this review assesses its impacts and identifies escalating policy issues. To provide a comprehensive literature review of small hydropower, we evaluated over 3600 articles and policy documents. This review identified four major concerns: (1) confusion in small hydropower definitions is convoluting scholarship and policy-making; (2) there is a lack of knowledge and acknowledgement of small hydropower's social, environmental, and cumulative impacts; (3) small hydropower's promotion as a climate mitigation strategy can negatively affect local communities, posing contradictions for climate change policy; and (4) institutional analysis is needed to facilitate renewable energy integration with existing environmental laws to ensure sustainable energy development. For readers interested in small hydropower, we clarify areas of confusion in definition and explain the corresponding impacts for distinct system designs. For a broader readership, we situate small hydropower implementation within international trends of renewable energy development – the contradictory impacts of climate change policy, emerging dynamics in energy finance, and reliance on market mechanisms. Our paper provides a timely contribution to scholarship on small hydropower and the transition to renewable energy. Highlights: Confusion in small hydropower definitions is convoluting small hydropower debates. Small hydropower's negative impacts are largely overlooked in policy discussions. Small hydropower exemplifies paradoxical problems with climate change policy. Policies needed to integrate renewable energy development with national environmental institutions.